Dataset on free amino acids contents of Serra da Estrela PDO cheeses determined by UPLC-DAD-MS/MS - Lima, M.J. Reis (2020)
The composition of Serra da Estrela PDO cheeses (total fat, total protein, salt and free amino acids) was assessed using NIR spectrophotometry and UPLC-DAD-MS/MS. In total, 24 cheeses were acquired from 6 certified cheesemakers located in 5 different municipalities within the delimited PDO geographical region. Cheeses were produced from raw ewe milk of two autochthonous Portuguese sheep breeds, between November 2017 and March 2018, and were acquired after 45 days of maturation. The data include the mean (and respective standard deviations) levels of moisture (%), total fat (%), total protein (%) and salt (%), obtained by NIR spectrophotometry. As well the mean (and respective standard deviations) of free amino acids contents (mg/100 g of cheese, in wet basis) evaluated using a UPLC-DAD-MS/MS method are shown. The latter data include information regarding 8 essential free amino acids (histidine, leucine-isoleucine, lysine, methionine, phenylalanine, threonine, tryptophan and valine) and 9 non-essential free amino acids (arginine, asparagine, aspartic acid, cysteine, glutamine, glutamic acid, proline, tyrosine and serine). Leucine and isoleucine, being isomers, were quantified together. Leucine-isoleucine, phenylalanine and serine were the most abundant essential free amino acids and cysteine, proline and asparagine were the most abundant non-essential free amino acids. Free amino acids contents depended on the cheese producer as well as on the production time-period.